ALGORITMO COMPUTACIONAL PARA CÁLCULO DO NÚMERO ÚNICO DE ISOLAMENTO ACÚSTICO PARA A AVALIAÇÃO DO ISOLAMENTO ACÚSTICO EM EDIFICAÇÕES E ELEMENTOS CONSTRUTIVOS SEGUINDO A ISO 717:2013 - Barbiere Júnior, Marcos Roberto (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Brazilian standard for buildings performance require as measurement for sound insulation assessment a single-number value for sound insulation rating by the method of comparison at ISO 717, parts 1 and 2. The calculating for this method can be facilitated when the computer algorithm suggested in this paper is applied. The algorithm is exposed with a simple and flexible structure for an easier implementation at different programming languages. The results obtained through the algorithm are fast, accurate and reliable. This algorithm also can be used in many TI areas.